(untitled) (International journal of medical sciences, 2025)
SGLT2 inhibitors have been shown to lower the risk of heart failure (HF) in people with diabetes, improving outcomes for HF patients across all levels of left ventricular ejection fraction (LVEF). This is achieved by reducing HF exacerbations and the risk of cardiovascular death. However, there is still uncertainty regarding the mechanisms responsible for these benefits beyond the inhibition of the sodium-glucose cotransporter 2 (SGLT2). Limited studies have explored the effects of SGLT2 inhibitors on cardiac remodeling through imaging and specific biomarkers, particularly in HF patients, with existing findings being inconclusive and primarily focused on those with diabetes and reduced LVEF. Importantly, there is a lack of data examining how SGLT2 inhibitors influence cardiac geometry, function, and biomarkers in the context of HF, regardless of LVEF. Adverse remodeling of the myocardium, especially in the left ventricle, is a critical factor in the progression of HF, which is typically classified based on LVEF. However, other aspects, such as the left atrium’s role, are often overlooked. The left atrium significantly impacts cardiac function, especially concerning left ventricular filling during the diastolic phase. Dysfunction of the atrium can directly contribute to pulmonary congestion. Atrial remodeling occurs in HF irrespective of the extent of left ventricular systolic dysfunction and can be identified in both preserved and reduced LVEF cases. The morphology of the left atrium has been linked to the risk of developing HF in high-risk individuals and has been associated with increased rates of hospitalization and mortality among HF patients. Consequently, atrial health has become an essential focus in recent European Society of Cardiology (ESC) guidelines for HF. This study aims to examine the effect of SGLT2 inhibitors on cardiac remodeling parameters, with a specific focus on left atrial remodeling, in patients with HF, independent of their LVEF status.